2021
DOI: 10.1155/2021/8156288
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Value of Body Mass Index and Waist-Hip Ratio in Clinicopathological Characteristics and Prognosis of Uterine Leiomyomata

Abstract: Objective. To explore the relationship between body mass index (BMI) and waist-to-hip ratio (WHR) and clinicopathological characteristics and prognosis of uterine leiomyomata (UL). Methods. A retrospective analysis of the clinical data of 133 patients with UL admitted to our hospital from September 2018 to August 2019. According to the BMI standard, the patients were divided into the normal group (n = 32), the super-recombination group (n = 45), and the obesity group (n = 56). According to WHR, the patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Amongst women who had their fibroids surgically removed, the presence of elevated BMI and waist to hip ratio (WHR) were found to be associated with a higher incidence of multiple-and larger fibroids. (Pan et al 2021) A current higher BMI is positively correlated with an increased risk of fibroid occurrence. (Ciebiera et al 2016;Terry et al 2007;Wise et al 2005).…”
Section: Body Mass Indexmentioning
confidence: 95%